Optimization of dye removal from aqueous Remazol Brilliant Blue R (RBBR) by Trametessp. Pellets - Parviz Mohamadi (Journal of Applied Research in Water and Wastewater, 2014)
Decolorization of Remazol Brilliant Blue R (RBBR) by Trametessp. Pellets was studied in a batch reactor. Dye removal process was performed in shaken flasks which contained 100 ml of RBBR aqueous solution and fungal pellets. The process was followed for 48 h and the dye removal was analyzed at a visible spectrum of 590 nm. Response surface methodology (RSM) employing Box Behnken design at three factors i.e. initial concentration of RBBR, mass of pellet and pH was used to optimize the decolorization process) with three replicates. Response surface regression showed that the decolorization efficiency was affected by initial RBBR concentration. Mass of pellet and pH in this model were not found to be insignificant for both main and square effects. The dye decolorization varied within the range of 16.81% to 77.91%. The lowest decolorization was achieved in maximum initial concentration dye and pH. While the highest decolorization was observed when low initial dye concentration and pH were used. From the optimization, maximum dye removal efficiency of 67.9% ± 5.43 was achieved at 50 ppm RBBR solution, 4 gram of pellets at pH 5.6.